Novel Insights into the Distribution and Functional Aspects of the Calcium Binding Protein Secretagogin from Studies on Rat Brain and Primary Neuronal Cell Culture - Maj, Magdalena; Milenkovic, Ivan; Bauer, Jan; Berggard, Tord; Veit, Martina; Ilhan-Mutlu, Aysegül; Wagner, Ludwig; Tretter, Verena E. (Frontiers in Molecular Neuroscience, 2012)
Secretagogin is a calcium-binding protein highly expressed in neuroendocrine cells. It has been shown to be involved in insulin secretion from pancreatic beta cells and is a strong candidate as a biomarker for endocrine tumours, stroke and eventually psychiatric conditions. Secretagogin has been hypothesized to exert a neuroprotective role in neurodegenerative diseases like Alzheimer’s disease. The expression pattern of Secretagogin is not conserved from rodents to humans. We used brain tissue and primary neuronal cell cultures from rat to further characterize this calcium binding protein in rodents and to perform a few functional assays in vitro. Immunohistochemistry on rat brain slices revealed a high density of secretagogin-positive cells in distinct brain regions. Secretagogin was found in the cytosol or associated with subcellular compartments. We tested primary neuronal cultures for their suitability as model systems to further investigate functional properties of Secretagogin in a cellular background that is close to the conditions in native neuronal tissue. These cultures can easily be manipulated by treatment with biological agents and by transfection with heterologous constructs. We show that, like in pancreatic beta cells and insulinoma cell lines also in neurons the expression level of Secretagogin is dependent on extracellular insulin and glucose. Further, we show also for rat brain neuronal tissue, that Secretagogin interacts with the microtubule-associated protein Tau and that this interaction is dependent on Ca2+. Future studies should aim to study in further detail the molecular properties and function of Secretagogin in individual neuronal cell types, in particular the subcellular localization and trafficking of this protein and a possible active secretion by neurons.